DEVELOPMENT OF COGNITIVE AND CREATIVE ABILITIES OF STUDENTS OF THE FACULTY OF PHYSICAL CULTURE UNDER THE CONDITIONS OF TEACHING COMPLEX-COORDINATED PHYSICAL EXERCISES - Matveev, A.P.; Haider, Nayouf Gaidaa; Korolkov, A.N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal the influence of the "operational-circular information model" of teaching physical exercises on the development of creative and cognitive abilities of future physical education teachers. Methods and structure of the study. The work was carried out on the basis of the Moscow State Regional University in the period from 2018 to 2021. 24 students (boys and girls) of the Faculty of Physical Culture were involved in the study, who studied in the direction of training 44.03.01 "Pedagogical education" (training profile - Physical Culture). The technique was based on an operational-circular information model of training and was worked out by comparing the technique for performing a new exercise being learned with the technique of a reference sample. Results and conclusions. A structurally organized methodology, which includes blocks of physical, technical and technological training, allows for the period of study from the 2nd to the 4th semester to improve the indicators of students' cognitive abilities from 22 to 41%, and creative - from 19% to 51%. During the period of the experiment, the creative potential of the students of the experimental group improved on average from 47.9±0.98 to 67.4±2.13 (≤ 0.05).